DISTANCE LEARNING AND OBSTACLES DURING COVID-19 OUTBREAK - Chusna Apriyanti (Prodi PGSD FKIP Universitas Islam Sultan Agung, 2020)
This paper aims to know the implementation of distance learning during COVID-19 cases in Pacitan and to find out the obstacles in handling distance learning in Pacitan. This is phenomenological research. The data were collected by using an online interview with parents. There were 48 parents of kindergarten and elementary school students as the sample. The researcher selected the sample by using simple random sampling. The results showed that there were five implementations of distance learning: doing worksheets from school (15 students), joining online class/online sources from the internet (7 students), completing the task from school (18 students), doing free activities without guidance (4 students), doing free activities with guidance (7 students). However, there were eight obstacles faced by parents in implementing distance learning: the parents could not focus to guide children in learning (4 respondents), the children could not focus to their learning (10 respondents), the children got boredom (4 respondents), the children did not want to learn (10 respondents), the children wanted to watch the television or play games (4 respondents), the children asked to go to school (3 respondents), the children could not do online learning (7 respondents), and the children had limited understanding related to the material (3 respondents).